2000
DOI: 10.1038/77108
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-1 is required for Wnt-1-induced mammary tumorigenesis in mice

Abstract: Syndecan-1 is a cell-surface, heparan-sulphate proteoglycan (HSPG) predominantly expressed by epithelial cells. It binds specifically to many proteins, including oncoproteins. For example, it induces the assembly of a signalling complex between FGF ligands and their cognate receptors. But so far there has been no direct evidence that this proteoglycan contributes to tumorigenesis. Here we have examined the role of syndecan-1 (encoded by Sdc1) during mammary tumour formation in response to the ectopic expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
254
3
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(272 citation statements)
references
References 30 publications
12
254
3
3
Order By: Relevance
“…Thus, the reducing end residue (residue 4) of the tetrasaccharide is a 2-O-sulfated ⌬ 4,5 -uronic acid, provided that HS glycuronate-2-sulfatase specifically reacts with this residue (24). 5 Taken together, these results demonstrate that fraction D contains a tetrasaccharide with a structure of ⌬UA2S-GlcNS- 4 Two minor [ 35 S]peaks were also observed, representing [ 35 S]sulfate and IdoUA2S-AnMan3S, respectively. The IdoUA2S-AnMan3S is probably the partial desulfated IdoUA2S-AnMan3S6S because of nitrous acid degradation or the product of the minor contaminants in the fraction D. 5 It should be noted that we identified the positions of five sulfate groups in the reducing end tetrasaccharide to this end.…”
Section: Structural Characterization Of Fraction D Analysis Of Fractisupporting
confidence: 54%
See 2 more Smart Citations
“…Thus, the reducing end residue (residue 4) of the tetrasaccharide is a 2-O-sulfated ⌬ 4,5 -uronic acid, provided that HS glycuronate-2-sulfatase specifically reacts with this residue (24). 5 Taken together, these results demonstrate that fraction D contains a tetrasaccharide with a structure of ⌬UA2S-GlcNS- 4 Two minor [ 35 S]peaks were also observed, representing [ 35 S]sulfate and IdoUA2S-AnMan3S, respectively. The IdoUA2S-AnMan3S is probably the partial desulfated IdoUA2S-AnMan3S6S because of nitrous acid degradation or the product of the minor contaminants in the fraction D. 5 It should be noted that we identified the positions of five sulfate groups in the reducing end tetrasaccharide to this end.…”
Section: Structural Characterization Of Fraction D Analysis Of Fractisupporting
confidence: 54%
“…5). 4 The result suggests that the 3-O- 35 S-sulfation site is present in a disaccharide with a structure of -IdoUA2S-GlcNH 2 3S6S-, provided that a previous report (11) demonstrated that 3-OST-3A sulfates an N-unsubstituted glucosamine residue.…”
Section: Structural Characterization Of Fraction D Analysis Of Fractimentioning
confidence: 68%
See 1 more Smart Citation
“…In this regard, several different proteoglycans and/or their glycosaminoglycan chain components that are abundantly present at the cell surface have been reported to stimulate the Wnt/ÎČ-catenin pathway. These include free heparan sulfate (4), heparin chains (5-7), and heparan sulfate proteoglycans, such as glypican-3 (8) and syndecan-1 (9).…”
mentioning
confidence: 99%
“…It has been suggested that syndecan-1 is involved in Wnt-1 induced tumor in the mouse mammary gland (Alexander et al, 2000). It has been found that syndecan-1 promotes the metastases in lung squamous carcinoma cells (Hirabayashi et al, 1998).…”
Section: Soluble Syndecans and Tumormentioning
confidence: 99%